LABOR RIGHTS CONCERNING INAPPROPRIATE WAGE PAYMENT AGAINST PROVINCIAL MINIMUM WAGE (UMP) BASED ON LAW NUMBER 13 OF 2003 CONCERNING MANPOWER - Alfitran Alfitran (Universitas Muhammadiyah Ponorogo, 2020)
This research was intended so that the readers understood regarding ProvincialMinimum Wage (Upah Minimum Provinsi (UMP)) as in Law Number 13 of 2003concerning manpower in Indonesia. In that law, there is a provision which states thatemployers are prohibited from providing wages below the provincial minimum wagethat has been stipulated by provincial governors throughout Indonesia. If the employersprovide wage which is below the provincial minimum wage that is stipulated bygovernment, the employers will get sanction either in administrative sanction orimprisonment sanctions as what is regulated in article 185 of Law, Number 13 of 2003concerning manpower and it states that there are administrative sanctions andimprisonment sanctions